Citayam Fashion Week as the Cultural Identity of Jakarta’s Generation Z - Ichwan Hakim; suraya suraya (Ikatan Sarjana Komunikasi Indonesia, 2024)
Citayam Fashion Week gains pros and cons and represents the appearance of Jakarta's Generation Z streetwear that comes, gathers, shows off itself, and appears in these social situations. Citayam Fashion Week reinforces the streetwear fashion trend of Jakarta's Generation Z, which is formed from a process of cultural identity.Â This study aims to determine how cultural identity is formed in Generation Z Jakarta at Citayam Fashion Week. The theories used Fashion Communication theory, Intercultural Communication, Streetwear, and Cultural Identity. The paradigm used is the constructivism paradigm. This research is qualitative research with a research method using case studies. In this study, the primary data to be used is observation in the form of in-depth interviews directly with informants. The study results show that two types of Generation Z come to Citayam Fashion Week. The first is the generic, spontaneous one that comes without any interest, just looking for friends or entertainment. Her streetwear outfits are also mainstream, inspired by Hip Hop, R&B, and other subcultures. The second is Generation Z, whose intentions are for various interests such as existence, promoting work, comparing self-identities.